DEVELOPMENT OF HEAT-INSULATING COATINGS FOR DIE MOULD OF LOW-PRESSURE CASTING - A. A. Kosovich; T. R. Gilmanshina; T. A. Bogdanova; E. G. Partyko; D. Yu. Kritsky (Литьë и металлургия, 2017)
Influence of heat-insulating release coatings on quality of light-alloy wheels is considered. Comparison of properties of the developed compositions and foreign analogues is carried out. Computer simulation of wheel casting by low pressure method in the painted die mould is executed. Results of approbation of the developed composition under the conditions of existing industry are presented.